Generating high-quality single droplets for optical particle characterization with an easy setup. (26th April 2018) - Xu, Jie; Ge, Baozhen; Meng, Rui
Abstract: The high-performance and micro-sized single droplet is significant for optical particle characterization. We develop a single-droplet generator (SDG) based on a piezoelectric inkjet technique with advantages of low cost and easy setup. By optimizing the pulse parameters, we achieve various size single droplets. Further investigations reveal that SDG generates single droplets of high quality, demonstrating good sphericity, monodispersity and a stable length of several millimeters.